Where Have All the Union Members Gone? - Neumann, George R.; Rissman, Ellen R. (Journal of Labor Economics, 1984)
This paper examines trends in union membership during the twentieth century. The hypothesis is advanced that the provision of certain social welfare benefits by government substitutes for the private provision by unions, thereby reducing the attractiveness of union membership. The empirical implications of this hypothesis are examined using time-series data on aggregate union membership for the period 1904-80 and using pooled state data for the period 1964-80. These latter data are used to examine the effect of departures from the traditional doctrine of "employment at will." Both the time-series and the cross-section evidence suggest that government supply of "union-like" services reduces union membership.